LEARNING STATISTICS COURSE USING COMPUTER_AIDED SOFTWARE: A CASE STUDY AMONG FURNITURE TECHNOLOGY STUDENTS - Aszila Asmat; Syafiza Saila Samsudin; Sharifah Norhuda Syed Wahid (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Computer-aided software is one of the most promising innovations to improve the teaching and learning process. With the integration of modern information and communication technologies, various computer-aided software has been developed and used to facilitate students in various courses. This study only focusing on learning statistics courses with the use of Minitab software as a computer-aided software. Thus, to measure the effectiveness of learning statistics courses using the computer-aided software, 26 students who enrolled in statistics courses were selected. As a result, it is found that there is a significant improvement in students’ scores when Minitab software was used in the course. The average of score also showed improvement by more than 14 percent compared to the traditional approach. The positive impact of students’ performance indicated that computer-aided learning is more applicable to be implemented in many different courses, not only limited to statistics.